Excavations at St James's Priory, Bristol - Jackson, Reg (Historic England, 2006)
The Benedictine Priory of St James was established just outside the medieval city of Bristol in 1129AD. Two areas were excavated: Site 1 to the east of the Priory church, and Site 2 to the west. The Priory was largely destroyed during the Dissolution of 1540, but the area around Site 1 remained in use during the 17th and 18th centuries as housing was built there. Site 2 was in use from the late Saxon period to the 20th century. This publication presents the results of excavations carried out at Site 1 from 1989 and 1995, and from Site 2 from 1994 and '95, along with those obtained from a watching brief, kept during landscaping work in 1997. There are also specific chapters on finds and burials.